Seasonal recruitment and survival strategies of Palisada cervicornis comb. nov. (Ceramiales, Rhodophyta) in coral reefs. Issue 5 (15th August 2017) - Collado‐Vides, Ligia; Duran, Alain; Armenis, Elizabeth; Cassano, Valéria; Burkepile, Deron; Shantz, Andrew A.; Palma, Laura; Díaz‐Larrea, Jhoana; Sentíes, Abel; Fujii, Mutue Toyota
Abstract : As marine tropical ecosystems deteriorate and lose biodiversity, their communities are shifting to being dominated by a few species, altering ecosystem's functioning and services. Macroalgae are becoming dominant on coral reefs, and are frequently observed outcompeting corals. Turf algal assemblages are the base of energy flow in these systems and one of the most abundant types of macroalgae on coral reefs, but little is known about their biology and diversity. Through molecular and morphological analyses, we identified the turf‐forming species Laurencia cervicornis, and by studying seasonal recruitment and the impact of herbivorous fishes on its abundance, we describe its survival strategy. The molecular analyses used a total of 45 rbc L gene sequences including eight current genera within the Laurencia complex and two new sequences of L. cervicornis and strongly support the new combination of Palisada cervicornis comb. nov. In addition, a detailed morphological characterization including the description of reproductive structures is provided. Palisada cervicornis was seen recruiting in all seasons but was typically in low abundance. Specimens grown on tiles in fish exclosure cages were devoured in less than 4 h when offered to fishes. Even though many species of the Laurencia complex have chemicals that deter herbivory, species within the genus Palisada lack feeding deterrents and thus are highly palatable. We suggest that P. cervicornis is a palatable species that seems to survive in the community by obtaining a size‐refuge from herbivory within turf communities.